Hadis Nabi di Pesantren: Studi atas Pembelajaran Kitab al-Mawaiz al-Usfuriyah - Umi Aflaha; Andini Jelita Putri Kurniawan (Musala : Jurnal Pesantren dan Kebudayaan Islam Nusantara, 2025)
This article examines the study of the Prophet’s hadith in Islamic boarding schools (pesantren) through secondary hadith texts. Among these texts is al-Mawaiz al-Usfuriyah, also widely known as Arbain, due to its structure which compiles around forty hadiths. This study employs a descriptive-analytical method to explore: (1) the urgency and relevance of studying the Prophet’s hadith through al-Mawaiz al-Usfuriyah, and (2) the methods used in teaching al-Mawaiz al-Usfuriyah in pesantren. The article concludes that teaching al-Mawaiz al-Usfuriyah remains essential and relevant today. It continues to be an effective tool in pesantren for introducing the Prophet’s hadith in a simple, practical, and meaningful way—particularly for beginners and students. In pesantren, this book is often taught using the bandongan method rather than sorogan, as it is commonly studied during the month of Ramadan by students of various educational levels as part of efforts to engage in more positive and beneficial activities during fasting.